(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Case reports represent the oldest and most familiar form of medical communication. It is one of the best ways for the beginners to get familiar with scholarly writing. It is the time-honored vehicle for medical teaching. It is also the foundational ’building block’ of scientific inquiry. Unfortunately from late 1970s in scientific community there was a tendency to see the case report as least important and a ’second class’ publication. The authors tried to find out how this ’fertile seeds’ were cultivated and valued by the scientific community. Articles on case reports were collected consecutively by daisy chaining from web and published journals. Many logical arguments are found in favor of encouraging in writing and publishing case reports. There are also issues to be addressed further. Diversified criteria and stylescan be followed. Uniqueness is not the only principle, any information which someone find useful and beneficial in clinical practice can be presented as case report. Facts in a case report can be considered as one of the weakest evidence and should not be considered as anecdotal information. To make others aware of unusual presentationsor complications;case report is the rapid and effective means of communication. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 50-55